Ha-zno mixed nanofluid and preparation method thereof

CN122979032APending Publication Date: 2026-10-27SICHUAN UNIVERSITY OF SCIENCE AND ENGINEERING
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611169854.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-04
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

但是,羟基磷灰石纳米颗粒与纳米氧化锌颗粒在密度、粒径、表面电位及分散行为等方面存在差异,二者简单混合于水基及乳化液基体系中时,容易因相容性不足而发生颗粒团聚、沉降和分层,难以形成长期稳定的共分散状态

Benefits of technology

[0014]本发明的技术效果和优点:本发明通过将HA纳米颗粒与纳米ZnO颗粒按1:0.2-1:1的质量比复配,控制功能组分总浓度为0.1-3.0g/L,同时采用十二烷基硫酸钠(SDS)作为唯一分散剂与HA-ZnO功能组分在含量和比例上相互配合;结合机械搅拌与超声分散复合工艺及pH9.0-10.0精准调控,能够减少HA纳米颗粒与纳米ZnO颗粒因密度、表面电位和分散行为差异导致的团聚、沉降和分层现象。所得HA-ZnO混合纳米流体的Zeta电位绝对值≥30mV,静置72h后的沉降稳定系数K≥0.9,从而实现了HA纳米颗粒与纳米ZnO颗粒在水基及乳化液基体系中的共分散稳定性,并降低了因颗粒团聚、沉降导致切缝堵塞、放电短路及加工不稳定的风险。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979032A_ABST
    Figure CN122979032A_ABST
Patent Text Reader

Abstract

The application discloses a kind of HA-ZnO mixed nanofluid and preparation method thereof, belong to nanofluid preparation technical field.The nanofluid with deionized water or mass fraction 1%-3% emulsion as base fluid, with mass ratio 1:0.2-1:1 hydroxyapatite (HA) and nano ZnO particles as functional component (total concentration 0.1-3.0g / L), with sodium dodecyl sulfate (SDS) as dispersant (addition amount 0.03%-0.2%);By mechanical stirring and ultrasonic dispersion composite process and pH9.0-10.0 precision control preparation.The absolute value of Zeta potential of the obtained nanofluid is greater than or equal to 30mV, the sedimentation stability coefficient K is greater than or equal to 0.9 when standing for 168h (7 days), solve the long-term co-dispersion problem of two types of nanoparticles in water-based and emulsion-based system.When used for medical titanium alloy wire cut electrical discharge machining, it can effectively avoid the cutting seam blockage, and provide a basis for realizing precision forming and surface bioactivity-antibacterial modification integration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nanofluid preparation technology, and more specifically, to a HA-ZnO mixed nanofluid for medical titanium alloy electrical discharge wire cutting and its preparation method. Background Technology

[0002] Medical-grade titanium alloys, such as Ti-6Al-4V, have become commonly used materials for orthopedic and dental implants due to their excellent biocompatibility, high specific strength, and corrosion resistance. In the traditional fabrication of medical titanium alloy implants, precision forming and surface functionalization are usually performed in separate steps, resulting in a long process flow, high manufacturing costs, and insufficient bonding strength between the surface functional layer and the substrate. Powder mixing electrical discharge machining (EDM) technology can introduce functional powders during EDM, allowing functional particles or their constituent elements to participate in surface modification, making it possible to integrate medical titanium alloy processing and surface functionalization. However, in traditional powder mixing media, functional powders are prone to sedimentation, agglomeration, and stratification, leading to uneven particle concentration, kerf blockage, and affecting the consistency of the surface modified layer quality during processing.

[0003] In functional powders used for surface modification of medical titanium alloys, hydroxyapatite nanoparticles can provide bioactive elements such as Ca and P to the titanium alloy surface, which is beneficial to improving surface osseointegration performance; while nano-zinc oxide particles can provide Zn to the titanium alloy surface, which is beneficial to improving surface antibacterial properties. Therefore, introducing hydroxyapatite nanoparticles and nano-zinc oxide particles into the processing medium is expected to enable the processing medium to simultaneously provide both bioactive and antibacterial elements. However, hydroxyapatite nanoparticles and nano-zinc oxide particles differ in density, particle size, surface potential, and dispersion behavior. When they are simply mixed in water-based and emulsion-based systems, they are prone to particle agglomeration, sedimentation, and stratification due to insufficient compatibility, making it difficult to form a long-term stable co-dispersion state. Especially in the process of wire EDM, the medium needs to circulate and maintain uniform particle concentration. If hydroxyapatite nanoparticles and nano-zinc oxide particles cannot be stably co-dispersed, it can easily lead to uneven particle concentration and discontinuous supply of functional particles during processing, increasing the risk of kerf blockage, discharge short circuit, and processing instability.

[0004] Existing dispersion methods mostly employ single mechanical stirring or single ultrasonic dispersion, which are generally difficult to adapt to the dispersion characteristics of both hydroxyapatite nanoparticles and zinc oxide nanoparticles simultaneously. Commonly used dispersants (such as sodium dodecylbenzenesulfonate, sodium carboxymethyl cellulose, and polyvinylpyrrolidone) have insufficient compatibility with two-component nanoparticles. While single-component nanofluids can improve the suspension state of a certain type of particle, they cannot solve the problem of long-term stable co-dispersion of two types of nanoparticles with different properties in the same water-based and emulsion-based systems. Therefore, how to achieve long-term stable co-dispersion of hydroxyapatite nanoparticles and zinc oxide nanoparticles in water-based and emulsion-based systems has become an urgent technical problem to be solved in the preparation of HA-ZnO mixed nanofluids. Summary of the Invention

[0005] To overcome the aforementioned deficiencies of the prior art, the present invention provides an HA-ZnO mixed nanofluid and its preparation method, which solves the problems mentioned in the background art through the following scheme.

[0006] To achieve the above objectives, the present invention provides the following technical solution: a HA-ZnO mixed nanofluid, comprising a base liquid, functional components, and a dispersant; The base liquid is deionized water, or an emulsion prepared from deionized water and emulsifying paste, wherein the emulsifying paste accounts for 1%-3% of the total mass of the emulsion; The functional component is composed of hydroxyapatite (HA) nanoparticles and zinc oxide nanoparticles, wherein the mass ratio of the hydroxyapatite nanoparticles to the zinc oxide nanoparticles is 1:0.2-1:1, and the total concentration of the functional component in the HA-ZnO mixed nanofluid is 0.1-3.0 g / L. The dispersant is sodium dodecyl sulfate (SDS), and the amount of the dispersant added accounts for 0.03%-0.2% of the total mass of the HA-ZnO mixed nanofluid.

[0007] Preferably, the base liquid accounts for 99.5%-99.97% of the total mass of the HA-ZnO mixed nanofluid.

[0008] Preferably, the HA nanoparticles have a particle size ≤100nm.

[0009] Preferably, the nano-ZnO particles have a particle size ≤50nm.

[0010] Preferably, the absolute value of the Zeta potential of the HA-ZnO mixed nanofluid is ≥30mV.

[0011] Preferably, the sedimentation stability coefficient K of the HA-ZnO mixed nanofluid after standing for 72 hours is ≥0.9; wherein, the sedimentation stability coefficient K is calculated according to the formula K=(V0-V) / V0, where V0 is the initial suspension volume, V is the volume of the supernatant after standing for 72 hours, and the units of V0 and V are both mL.

[0012] Preferably, the HA-ZnO mixed nanofluid has a viscosity of 1-10 mPa·s at 25°C and an electrical conductivity of 2200-5000 μS / cm.

[0013] This invention also discloses a method for preparing the above-mentioned HA-ZnO mixed nanofluid, comprising the following steps: S1. Raw material pretreatment: HA nanoparticles and nano ZnO particles are vacuum dried at 60℃ for 2 hours. If an emulsion base is used, the emulsion paste is first added to deionized water and mechanically stirred at 300r / min for 15 minutes until completely dissolved to obtain an emulsion with a mass fraction of 1%-3%. The deionized water or the prepared emulsion is ultrasonically degassed at 100W power for 15 minutes. S2. Preparation of pre-dispersion system: Add dispersant to deionized water or emulsion in step S1, and mechanically stir at 300-500 r / min for 20-30 min; then add HA nanoparticles and continue mechanical stirring for 30 min to obtain HA pre-dispersion system; S3. Composite dispersion and particle size refinement: Add nano-ZnO particles to the HA pre-dispersion system in step S2, slowly add 1 g / L KOH solution dropwise to adjust the pH value of the system to 9.0-10.0, first mechanically stir at 400 r / min for 20 min, and then ultrasonically disperse at a power of 150-200 W and a frequency of 20-40 kHz for 30-60 min, during which the system temperature is controlled ≤40℃ to obtain HA-ZnO mixed nanofluid; S4. Finished product storage: Add the HA-ZnO mixed nanofluid obtained in step S3 dropwise to 1g / L KOH solution to adjust the pH value to 9.0-9.5, then seal and store in a light-proof container, with the ambient temperature controlled at 15-25℃.

[0014] The technical effects and advantages of this invention are as follows: This invention combines HA nanoparticles and nano-ZnO particles at a mass ratio of 1:0.2-1:1, controlling the total concentration of functional components to 0.1-3.0 g / L. Sodium dodecyl sulfate (SDS) is used as the sole dispersant, complementing the HA-ZnO functional components in terms of content and ratio. Combined with mechanical stirring and ultrasonic dispersion processes, and precise pH control between 9.0-10.0, this reduces agglomeration, sedimentation, and stratification phenomena caused by differences in density, surface potential, and dispersion behavior between HA nanoparticles and nano-ZnO particles. The resulting HA-ZnO mixed nanofluid has an absolute Zeta potential ≥30 mV and a sedimentation stability coefficient K ≥0.9 after standing for 72 h. This achieves stable co-dispersion of HA nanoparticles and nano-ZnO particles in water-based and emulsion-based systems, and reduces the risks of kerf blockage, short circuits, and processing instability caused by particle agglomeration and sedimentation. Attached Figure Description

[0015] Figure 1 Photographs of the static stability of HA-ZnO mixed nanofluids with different dispersion systems at different time points after preparation (0h); Figure 2 For photos taken 24 hours after preparation; Figure 3 The image was taken 96 hours after preparation. Figure 4 The images were taken 168 days after preparation (7 days). The samples in each image, from left to right, are: emulsion-based group without dispersant (emulsion), deionized water-based group without dispersant (no), SDBS group, SDS group, CMC-Na group, and PVP group. Figure 5 The image shows the particle size distribution of HA-ZnO mixed nanofluids DLS in different dispersion systems; the horizontal axis represents the particle size (μm) of HA-ZnO mixed nanoparticles, and the vertical axis represents the intensity of scattered light (%). Detailed Implementation

[0016] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0017] I. Specifications of Raw Materials and Reagents The specifications of the raw materials and reagents used in the embodiments and comparative examples of this invention are as follows: Deionized water: prepared in the laboratory using RO membrane reverse osmosis, with a conductivity ≤6μS / cm; HA nanoparticles: commercially available, purity ≥99.9%, average particle size 80nm (provided by the seller), meeting the requirement of ≤100nm; Nano ZnO particles: Commercially available, purity ≥99.9%, average particle size 20nm (provided by the seller), meeting the requirement of ≤50nm; Sodium dodecyl sulfate (SDS): Commercially available, analytical grade, purity ≥99.0%; Sodium dodecylbenzenesulfonate (SDBS): Commercially available, analytical grade, purity ≥99.0%; Sodium carboxymethyl cellulose (CMC-Na): Commercially available, analytical grade, degree of substitution 0.6-0.8; Polyvinylpyrrolidone (PVP): Commercially available, K30 type, molecular weight 30000±5000; Potassium hydroxide (KOH): Commercially available, analytical grade, purity ≥85.0%, prepared as a 1 g / L aqueous solution; Emulsifying paste for electrical discharge machining: Commercially available, general-purpose wire cutting emulsifying paste.

[0018] II. Preparation of Examples and Comparative Examples All examples and comparative examples were prepared to a final volume of 1L.

[0019] Example 1: SDS Group (Optimal Example) 1. Raw materials and reagents Raw material dosage: 980g deionized water, 20g EDM emulsifying paste (prepared into an emulsion with a mass fraction of 2%), 1.8g HA nanoparticles, 1.2g nano ZnO particles, 0.3g SDS (corresponding to 0.03% of the total mass), and an appropriate amount of 1g / L KOH solution.

[0020] 2. Preparation method S1. Raw material pretreatment: HA nanoparticles and nano ZnO particles were vacuum dried at 60℃ for 2h; 20g of emulsion paste was added to 980g of deionized water and stirred at 300r / min for 15min until completely dissolved to obtain an emulsion with a mass fraction of 2%; the emulsion was ultrasonically degassed at 100W power for 15min.

[0021] S2. Preparation of pre-dispersion system: SDS was added to the emulsion after ultrasonic degassing, and mechanically stirred at 300 r / min for 25 min to dissolve and disperse the SDS evenly; then HA nanoparticles were added, and mechanical stirring was continued for 30 min to obtain the HA pre-dispersion system.

[0022] S3. Composite dispersion and particle size refinement: Add nano-ZnO particles to the HA pre-dispersion system obtained in step S2, slowly add 1 g / L KOH solution dropwise to adjust the pH value of the system to 9.0, and then mechanically stir at 400 r / min for 20 min; then start the ultrasonic dispersion device and ultrasonically disperse at 180 W power and 30 kHz frequency for 45 min, and use the constant temperature water bath method to control the system temperature at 35℃ to obtain emulsion-based HA-ZnO mixed nanofluid.

[0023] S4. Finished product storage: Add the HA-ZnO mixed nanofluid obtained in step S3 dropwise to 1g / L KOH solution to adjust the pH value to 9.0-9.5, then seal and store in a light-proof container at a temperature of 20℃.

[0024] Comparative Example 1: Emulsion-based group without dispersant ( Figure 1 (Middle "breast" group) The difference between this comparative example and Example 1 is that an emulsion is used as the base liquid, and no dispersant SDS is added.

[0025] The specifications, dosages, preparation steps, and process parameters of the other raw materials are exactly the same as those in Example 1.

[0026] Comparative Example 2: SDBS Group The difference between this comparative example and Example 1 is that sodium dodecylbenzenesulfonate (SDBS) is used as a dispersant, and the amount added is 0.3 g / L.

[0027] The specifications, dosages, preparation steps, and process parameters of the other raw materials are exactly the same as those in Example 1.

[0028] Comparative Example 3: CMC-Na Group The difference between this comparative example and Example 1 is that sodium carboxymethyl cellulose (CMC-Na) is used as a dispersant, and the amount added is 0.3 g / L.

[0029] The specifications, dosages, preparation steps, and process parameters of the other raw materials are exactly the same as those in Example 1.

[0030] Comparative Example 4: PVP Group The difference between this comparative example and Example 1 is that polyvinylpyrrolidone (PVP) is used as a dispersant, and the amount added is 0.3 g / L.

[0031] The specifications, dosages, preparation steps, and process parameters of the other raw materials are exactly the same as those in Example 1.

[0032] Comparative Example 5: Pure Emulsion Group The difference between this comparative example and Example 1 is that a pure emulsion is used, and no dispersant SDS and HA or ZnO particles are added.

[0033] The specifications, dosages, preparation steps, and process parameters of the other raw materials are exactly the same as those in Example 1.

[0034] III. Performance Testing The present invention conducted the following performance tests on the HA-ZnO mixed nanofluids of Example 1 and each comparative example. All tests were conducted at room temperature of 25°C.

[0035] 3.1 Performance Testing Methods 1. Settlement stability test Test method: Take 6 mL of freshly prepared nanofluid into a 10 mL colorimetric tube, seal it and let it stand vertically for 72 h (starting from 0 h when the preparation is completed), record the volume V of the supernatant, and calculate the sedimentation stability coefficient K according to the formula K=(6-V) / 6; the larger the K value, the better the sedimentation stability.

[0036] 2. Comparison of dispersants and DLS particle size distribution test Test Method: Particle size distribution testing was performed on a Bettersize3000Plus laser / image particle size and shape analyzer, according to the ISO 13320 standard for laser diffraction particle size analysis. The equivalent refractive index of the ZnO / HA composite powder was input as 1.82, and the extinction coefficient as 0.01. The instrument automatically aligns the optical path and measures the background. The sample was added dropwise slowly, with the shading rate controlled at approximately 17%. The sample was ultrasonically dispersed for 3 minutes to break up particle agglomerations. Each sample was tested in triplicate, and the average value was used to obtain D10, D50, D90, and the particle size distribution curve.

[0037] 3. Zeta potential, viscosity and conductivity testing Test methods: Zeta potential was measured using a U-tube interface migration electrophoresis apparatus; viscosity was measured using a rotational viscometer at a speed of 60 r / min; conductivity was measured using a conductivity meter.

[0038] 4. Verification of wire electrical discharge machining Test method: Ti-6Al-4V titanium alloy samples (10mm×10mm×5mm) were processed using a DK7732 high-speed wire EDM machine. Processing parameters: pulse width 8μs, pulse interval 10μs, number of power amplifiers 3, wire feed speed 10m / s, dielectric circulation flow rate 10L / min. The discharge waveform was acquired in real time using an oscilloscope during the processing, and the process was carried out continuously for 30min.

[0039] 3.2 Performance Test Results 1. Settlement stability In Example 1, after standing for 96 hours, there was no significant sedimentation. The volume of the supernatant was V = 0.3 mL, and K = 0.95 was calculated. The highest K value in the parallel sample test reached 0.96, which was the highest among all groups. Sedimentation stability coefficients of each comparative example: Comparative Example 1 (emulsion base without dispersant) K = 0.67, Comparative Example 2 (SDBS) K = 0.78, Comparative Example 3 (CMC-Na) K = 0.08, Comparative Example 4 (PVP) K = 0.83, Comparative Example 5 (pure emulsion) K = 0.67.

[0040] 2. Particle size distribution Emulsion-based group without dispersant: The second peak is in the 10-100μm range, indicating that a large number of particles have agglomerated and formed micron-sized large particles, resulting in very poor dispersion stability; SDBS group: The distribution is still relatively wide, with obvious distribution of small particles (<1μm) and medium-sized aggregated particles (1-10μm). The proportion of large particles has decreased, but obvious aggregation still exists, and the dispersion effect is average. SDS group: The main peak is concentrated in the 0.5-1μm range, and the intensity of scattered light accounts for more than 35%, indicating that most particles are in a small size state close to the original particle size; the intensity of micron-sized large particles is extremely low and can be ignored, which is the best dispersion effect among all groups; CMC-Na group: A very obvious bimodal distribution was observed, and the position of the second peak shifted to the 10-100μm range. There were even large particle peaks with an intensity >10%, indicating that the particle aggregation was very serious and the dispersion effect was the worst among all groups. PVP group: The peak value is concentrated around 1μm, the distribution width is narrow, the proportion of large particles is extremely low, and the dispersion effect is second only to SDS group, which is significantly better than the group without dispersant and SDBS group.

[0041] 3. Zeta potential, viscosity, and conductivity The Zeta potential of Example 1 was -46mV (absolute value ≥30mV), the viscosity was 1.65mPa・s, and the conductivity was 4800μS / cm.

[0042] 4. Verification of wire electrical discharge machining Test results: The discharge waveform was stable during the processing, with consistent pulse height and regular intervals. No short-circuit pulses or arc pulses were observed. After processing, there was no particle accumulation or blockage, and no burn marks were found on the surface.

[0043] The above embodiments are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A HA-ZnO hybrid nanofluid, characterized in that, include: Base liquid, functional components, and dispersants; The base liquid is deionized water, or an emulsion prepared from deionized water and emulsifying paste, wherein the emulsifying paste accounts for 1%-3% of the total mass of the emulsion; The functional component is composed of hydroxyapatite (HA) nanoparticles and zinc oxide nanoparticles, wherein the mass ratio of the hydroxyapatite nanoparticles to the zinc oxide nanoparticles is 1:0.2-1:1, and the total concentration of the functional component in the HA-ZnO mixed nanofluid is 0.1-3.0 g / L. The dispersant is sodium dodecyl sulfate (SDS), and the amount of the dispersant added accounts for 0.03%-0.2% of the total mass of the HA-ZnO mixed nanofluid.

2. The HA-ZnO mixed nanofluid according to claim 1, characterized in that, The base liquid accounts for 99.5%-99.97% of the total mass of the HA-ZnO mixed nanofluid.

3. The HA-ZnO mixed nanofluid according to claim 1, characterized in that, The HA nanoparticles have a particle size ≤100nm.

4. The HA-ZnO mixed nanofluid according to claim 1, characterized in that, The nano-ZnO particles have a particle size ≤50nm.

5. The HA-ZnO mixed nanofluid according to claim 1, characterized in that, The absolute value of the Zeta potential of the HA-ZnO mixed nanofluid is ≥30mV.

6. The HA-ZnO mixed nanofluid according to claim 1, characterized in that, The sedimentation stability coefficient K of the HA-ZnO mixed nanofluid after standing for 168 hours is ≥0.9; wherein, the sedimentation stability coefficient K is calculated according to the formula K=(V0-V) / V0, where V0 is the initial suspension volume and V is the volume of the supernatant after standing for 72 hours, and the units of V0 and V are both mL.

7. The HA-ZnO mixed nanofluid according to claim 1, characterized in that, The HA-ZnO mixed nanofluid has a viscosity of 1-10 mPa·s at 25℃ and an electrical conductivity of 2200-5000 μS / cm.

8. A method for preparing HA-ZnO mixed nanofluid according to any one of claims 1-7, characterized in that, Includes the following steps: S1. Raw material pretreatment: HA nanoparticles and nano ZnO particles were vacuum dried at 60℃ for 2 hours. If an emulsion base is used, first add the emulsion paste to deionized water and mechanically stir at 300 r / min for 15 min until completely dissolved to obtain an emulsion with a mass fraction of 1%-3%; then ultrasonically degas the deionized water or the prepared emulsion at 100W power for 15 min. S2. Preparation of pre-dispersion system: Add dispersant to deionized water or emulsion in step S1, and mechanically stir at 300-500 r / min for 20-30 min; then add HA nanoparticles and continue mechanical stirring for 30 min to obtain HA pre-dispersion system; S3. Composite dispersion and particle size refinement: Add nano-ZnO particles to the HA pre-dispersion system in step S2, slowly add 1 g / L KOH solution dropwise to adjust the pH value of the system to 9.0-10.0, first mechanically stir at 400 r / min for 20 min, and then ultrasonically disperse at a power of 150-200 W and a frequency of 20-40 kHz for 30-60 min, during which the system temperature is controlled ≤40℃ to obtain HA-ZnO mixed nanofluid; S4. Finished product storage: The HA-ZnO mixed nanofluid obtained in step S3 is sealed and stored in a light-proof container, and the ambient temperature is controlled at 15-25℃.